Planejamento e avaliação em manutenção e melhoria de redes de distribuição de energia, com base em indicadores operacionais - Martins, Lisandra Flores (2016)
Through the privatization of power sector infrastructure in Brazil, which was started in the country in the 1990s, the electricity sector, key to the development of the economy, is now regulated by the National Electric Energy Agency (ANEEL), and it goes through constant regulatory changes with order to ensure the quality of supply. One of the changes was the creation of the X factor, which determines the amount of minimum tax investments to electricity distributors. This stimulated large investments in this sector. Motivated by the need to direct these investments into work on distribution networks of large distributors, thus, there is the need to create analysis tools, based on criteria of intervention points in the network that would bring better return in terms of indicators and operational quality. The hypothesis is that, even the works of less investment, once they are made on the right spot, it can bring suitable results for the indicators of the leadership. Therefore, this research has characterized the process of targeting used, diagnosed the operational problems, and the risks involved in this model. Obtaining these results, a proposal for the management and investment targeting was presented, as well as the monitoring of these results, comparing them with the current model, based on multicriteria method ELECTRE II to decision making. This situation was based on current data of the Electrical System of a company, and the system responsible for their supply, in order to recommend the premises for future actions in the electrical system seeking to improve quality indicators. This study includes technical and operational systems of the company, taking into consideration the reliability criteria, the compensation paid, charging sets, equipment and conductors, voltage levels, technical losses and continuity indicators.